PENINGKATAN PERILAKU BERKARAKTER DAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IX MTsN MODEL PADANG PADA MATA PELAJARAN IPA-FISIKA MENGGUNAKAN MODEL PROBLEM BASED INSTRUCTION - Afrizon, Renol; Ratnawulan, Ratnawulan; Fauzi, Ahmad (Universitas Negeri Padang, 2012)
Problems are often encountered in learning science Physics in class IX of MTsN Model Padang is the process of learning science Physics is less meaningful because the matter is less related to problems in daily life. This indicates that the behavior of character and critical thinking skills students in grade IX is still low. In addition, variations in the model / learning methods are applied to teachers in the classroom learning process is still lacked. The purpose of this study is to improve character’s behavior and critical thinking skills of students in grade IX MTsN Model Padang on Physics science use Problem Based Instruction model. This type of study is classroom action research. The research was carried out in class IX. 9 MTsN Model Padang in two cycles that began in November 2011 to December 2011. Data obtained through the research instrument, namely: the behavior observation sheet character, character’s behavior is limited questionnaire given to students each end of the cycle, and critical thinking skills test is conducted every meeting and analyzed by percentage analyze techniques (%). The study found there was an increase of 15.39% characterized the behavior of the criteria began to develop into 45.61% of students are on begins to develop criteria (MB), and 21.84% on the custom criteria (MK). Analysis of the character’s behavior questionnaire also showed that an increase of 38.71% criteria began to grow (MB) and 1.79% in the custom criteria (MK) to 59.15% in the criteria began to grow (MB) and 7.84% the criteria into the habit (MK). The analysis of critical thinking skills showed that there was an increase from 54.62 to 11.37 percentage completeness with a percentage of 75.14% to 63.91% completeness. Based on the research results can be concluded that the application of the model problem based instruction can improve students' behavior that characterized the impact on critical thinking skills. Keywords: Problem Based Instruction model, Character’s Behavior and Critical Thinking Skills.